Hukum Ketenagakerjaan di Era Modern: Antara Hak dan Kewajiban - Fadil Muhammad (Universitas Muhammadiyah Magelang, 2024)
In today's modern era where all kinds of needs, especially in the world of work, must be available very quickly, causing complexity in work culture that is felt to require its own special rules, this study aims to explain the various phenomena faced by the employment sector in the modern era today, studied from the prevailing laws and regulations. This study is expected to be part of the references and guidelines related to changes or updates to employment law in the future. The research method used in this article is normative juridical with data collection techniques through literature studies from various sources in the form of laws and regulations, journal articles, and news that exist according to the context of employment developments in the modern era. With various phenomena and work cultures that exist in the modern era, a regulation is needed that can truly provide legal certainty with the aim of providing welfare and ensuring the rights and obligations of workers and companies in particular and evenly for the sake of increasing Indonesian human resources.